2019
DOI: 10.1037/men0000211
|View full text |Cite
|
Sign up to set email alerts
|

Men’s health-risk and protective behaviors: The effects of masculinity and masculine norms.

Abstract: Previous research has examined men's health in relation to women's functioning and compared morbidity and mortality rates among specific subgroups of men using demographic features. More recent research expands these approaches by also examining how men's thoughts, attitudes, and behaviors influence health-related attitudes and behaviors. The endorsement and internalization of masculinity is generally associated with more negative health behaviors and engagement in fewer health-protective behaviors. However, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 61 publications
(137 reference statements)
1
30
0
1
Order By: Relevance
“…This misinformation illustrated the lack of understanding about perceived timing, risk, and the severity of HPV-related illness ( Hunter & Weinstein, 2016 ; Pitts et al, 2017 ; Priest et al, 2015 ; Ratanasiripong, 2015 ). The lack of perceived risk ( Fontenot et al, 2014 ; Hunter & Weinstein, 2016 ; Pask & Rawlins, 2016 ) was directly related to both lack of awareness and the well-documented absence of sexual health-seeking behaviors typically seen in young males ( Salgado et al, 2019 ). Lack of HPV knowledge combined with high-risk sexual behaviors in late adolescence and early adulthood highlight the need for health promotion strategies to prevent life-changing illnesses ( Crocker et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This misinformation illustrated the lack of understanding about perceived timing, risk, and the severity of HPV-related illness ( Hunter & Weinstein, 2016 ; Pitts et al, 2017 ; Priest et al, 2015 ; Ratanasiripong, 2015 ). The lack of perceived risk ( Fontenot et al, 2014 ; Hunter & Weinstein, 2016 ; Pask & Rawlins, 2016 ) was directly related to both lack of awareness and the well-documented absence of sexual health-seeking behaviors typically seen in young males ( Salgado et al, 2019 ). Lack of HPV knowledge combined with high-risk sexual behaviors in late adolescence and early adulthood highlight the need for health promotion strategies to prevent life-changing illnesses ( Crocker et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gendered health behaviors are learned and may be socialized in men from an early age, reinforced during adolescence, and amplified in early adulthood ( Crocker et al, 2019 ). Studies have demonstrated that aligning to traditional masculine norms predicts men’s low rates of engagement in preventative health behaviors, such as routine medical exams, self-care practices, and psychological help ( Salgado et al, 2019 ). Men who do disclose engaging in sexual health promoting practices risk being characterized as “feminine” or “weak” ( Salgado et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations